Az Alföld és az új európai területfejlesztési perspektívák - Csatári, Bálint (Tér és Társadalom, 1998)
The Great Hungarian Plain is one of the most contradictory large regions in Hungary. The particular features of its historical development, the environmental hazards, the transitory crisis of the agri-business and the economy in the region, the extremely underdeveloped, peripheral situation of several micro-regions – on the other hand, the rapid catching up and development of a few towns in the region and the gradual appreciation of its transport corridors, considering that the Great Plain will be the Eastern border region of the European Union after the enlargement: all these factors underline the importance of the "difference", the uniqueness of the Great Hungarian Plain. The Great Plain is homogeneous from the aspect of quite a large number of regional factors, and its natural borders reach beyond the country borders. The development of the region involves many elements which require a brand new view and approach from both the regional policy of Hungary and the countries adjacent to the Great Plain. The study is actually a train of thoughts, partly established by regional and municipal surveys, which compares the future possibilities of the Great Hungarian Plain to the new, European level spatial approaches stated in the document called "European Spatial Development Perspectives", accepted in 1997. The main finding of the paper is that the endowments and possibilities of the Great Hungarian Plain, lying in its individual regional, environmental, economic, transport and social situation and its seftlement network, are better suited to these new, more subtle European structural and cohesion principles than the former, often mechanical, equalisation systems. New and successful regional development solutions are offered for the Great Plain by the integration to the Trans-European Networks (TEN-s), a complementary urban development, the promotion of the relationship between the towns and their rural hinterlands, the dissemination of innovation and knowledge, and the preservation and creative management of the environmental and cultural heritage. The spatial development of the Great Hungarian Plain, with a view to the shaping Carpathians and the Danube–Tisza–Körös–Maros Euro-regions, has definite "European dimensions", as well.